Peran Auditor Internal dalam Pendeteksian dan Pencegahan Fraud pada Bank Syariah di Kota Metro - Alika Nuri Syahiroh; Alya Nafiza; Anisa Martha Sujiva; Fikri Rizki Utama (Indo Publishing, 2026)
This study discusses the role of internal auditors in the detection and prevention of fraud in Islamic banking, with a focus on the context of Islamic banking in Metro City. The research was conducted using a descriptive qualitative approach through a library research method to understand the duties and responsibilities of internal auditors in maintaining the effectiveness of internal control systems within Islamic banking institutions. The research data were obtained from various secondary sources such as scientific journals, books, articles, and previous studies related to internal auditing and fraud prevention in Islamic banking. The results of the study indicate that internal auditors play an important role in detecting fraud through routine audits, transaction monitoring, financial statement analysis, and evaluation of bank operational procedures. Internal auditors also contribute to fraud prevention efforts by strengthening internal control systems, providing recommendations for improvement, and increasing employee awareness regarding the importance of integrity and compliance with company regulations as well as Islamic principles. In addition, this study shows that an effective internal control system can help minimize the risk of fraud in Islamic banking. However, this study also indicates several obstacles in the implementation of internal audit activities, such as limited human resources, the increasing complexity of fraud methods, time constraints in the audit process, and the lack of employee awareness regarding compliance with operational procedures. Therefore, improving auditor competence and strengthening internal control systems are considered important to support the effectiveness of fraud prevention in Islamic banking.